The Influence of Engagement Drivers and Personal Values toward Teachers Engagement Behavior at Sekolah Alam Bandung (The Indonesian Journal of Business Administration, 2021)
Employee engagement has become an essential topic in Human Resource management studies because it is related to employee loyalty and enthusiasm at work, which affect company performance. The primary purpose of this research is to find out how the influence of Employee Engagement Drivers and Personal Value (additional of Engagement Driver) towards Engagement Behavior, namely SAY (Speak positively about the organization to co-workers, potential employees, and customers), STAY (have an intense sense of belonging). and desire to be a part of the organization). Moreover, STRIVE (motivated and exert extra effort and engagement in work contributes to business success) at Sekolah Alam Bandung’s teachers. This research uses a descriptive quantitative method with multiple regression analysis techniques. The data that is processed beforehand is tested for validity, reliability, multicollinearity, autocorrelation, and heteroscedastic. The test results have met the requirements for further analysis. The sampling technique used a census (total sampling) by taking the entire sample with 34 teachers of Sekolah Alam Bandung (SAB).The results of the Coefficient Determination (R Square) test show that all operational variables of the Employee Engagement Driver consisting of Company Brand, Leadership, Performance, the Work, the Basic, Company Practice and Personal Value have a simultaneous effect on Say, Stay and Strive Behavior, with respective values of 91.8%, 92.2%, and 83.8%. Based on the t-test, which is to test how the Engagement Drivers influence Engagement Behavior partially. The “t” test results show that most influencing Say Behavior is Company Brand (Reputation). Meanwhile, the Engagement Drivers that most influencing Stay Behavior is Company Practice (Diversity & Inclusion and Communication). In addition, the most Engagement Drivers that influencing Strive Behavior is Leadership (Coaching).Keywords: Sekolah Alam Bandung, Employee Engagement Drivers, Employee Engagement Behavior, Personal Value.